Perancangan Aplikasi Layanan Pendaftaran Dokter Gigi Berbasis Website Menggunakan Metode Waterfall dan Regression - Siti widiyati malihah; Wawan Kurniawan (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The development of information technology has encouraged digital transformation in the health care sector, one of which is through a website-based dentist registration service application. J&J Dental Clinic is a clinic located in Jakarta and was established to support the health aspects and dental health services for the general public. This research aims to design and test the system using the Waterfall development method and Regression Testing. The Waterfall method was chosen because it is able to provide a structured and systematic development flow, while Regression Testing is used to ensure the stability of the system after adding or modifying features. Testing was conducted by 200 users on five main features of the system, including new patient registration, login/logout, reservations, financial reports, and admin data management. The test results showed that the average system success rate was above 97%, with the admin data management feature achieving 100% success and the financial report feature having the lowest success rate of 95%. These results prove that the application functions well and is stable, but still has room for improvement on some features. These findings can be the basis for further development of a reliable and user-friendly digital-based healthcare system.